2015
DOI: 10.1021/acs.langmuir.5b01647
|View full text |Cite
|
Sign up to set email alerts
|

Nonfreezing Water Structuration in Heteroprotein Coacervates

Abstract: Surface-bound water in protein solutions has been identified with a reduction in its freezing point. We studied the presence of such nonfreezing water (NFW) in various protein-polyelectrolyte, micelle-polyelectrolyte, and protein-protein (heteroprotein) coacervates, along with appropriate concentrated solutions of macromolecules alone, finding up to 15% w/w NFW for the heteroprotein coacervate of lactoferrin (LF) and β-lactoglobulin (BLG). The level of NFW is always higher in coacervates than in the control (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…Despite significant interest in and importance of the low interfacial tension of complex coacervate fluids, as highlighted, few systematic experimental studies exist that report on its physical basis, and even fewer that comprehensively combine experiments and theoretical considerations [54,74,[98][99][100]. We will highlight one most recent example published by the authors that showcase how one can gain access to key physical properties of complex coacervate fluids.…”
Section: Complex Coacervate With a Bicontinuous Fluid Structure And Ultra-low Cohesive Energymentioning
confidence: 98%
“…Despite significant interest in and importance of the low interfacial tension of complex coacervate fluids, as highlighted, few systematic experimental studies exist that report on its physical basis, and even fewer that comprehensively combine experiments and theoretical considerations [54,74,[98][99][100]. We will highlight one most recent example published by the authors that showcase how one can gain access to key physical properties of complex coacervate fluids.…”
Section: Complex Coacervate With a Bicontinuous Fluid Structure And Ultra-low Cohesive Energymentioning
confidence: 98%
“…For instance, calorimetry measurements have suggested that the "non-freezing water" content of protein-based coacervates could be as high as 15% w/w. 89 4. The solvent is assumed to be a continuum.…”
Section: Voorn-overbeek Treats Salts Polymers As Point Particlesmentioning
confidence: 99%
“…To date, the majority of approaches rely on indirect phenomenological measurements such as changes in the phase behavior of coacervates, 40,64,139 differences in the amount of water introduced into a sample by different ions, 53 or measurements of "non-freezing," surface-bound water. 89 Experimentally, new techniques such as terahertz dielectric spectroscopy have the potential to help directly access these structural changes, 149,150 and these questions look to be key to future materials design questionseven beyond coacervation.…”
Section: Key Experimental Challengesmentioning
confidence: 99%
“…At low temperature (e.g. 5°C), the hydrophobic tail dissociates leading to monomeric complexes formed by one LF and one concentration [68]. These authors suggest that protein assemblies constituting the coacervates maximize protein-water interactions.…”
Section: Primary Units Of the Coacervatesmentioning
confidence: 99%